Assessment of genetic diversity among surian Toona sinensis Roem in progenies test using random amplified polymorphic DNA markers - Jayusman Jayusman; Muhammad Na’iem; Sapto Indrioko; Eko Bhakti Hardiyanto; ILG Nurcahyaningsih (Universitas Gadjah Mada, 2017)
Surian Toona sinensis Roem is one of the most widely planted species in Indonesia. This study aimed to estimate the genetic diversity between a number of surian populations in a progeny test using RAPD markers, with the goal of proposing management strategies for a surian breeding program. Ninety-six individual trees from 8 populations of surian were chosen as samples for analysis. Eleven polymorphic primers (OP-B3, OP-B4, OP-B10, OP-H3, OP-Y6, OP-Y7, OP-Y8, OP-Y10, OP-Y11, OP-Y14, and OP-06) producing reproducible bands were analyzed for the 96 trees, with six trees per family sampled. Data were analyzed using GenAlEx 6.3, NTSYS 2.02. The observed percentage of polymorphic loci ranged from 18.2% to 50%. The mean level of genetic diversity among the surian populations was considered to be moderate (He 0.304). Cluster analysis grouped the genotypes into two main clusters, at similarity levels of 0.68 and 0.46. The first two axes of the PCoA explained 46.16% and 25.54% of the total variation, respectively. The grouping of samples into clusters and subclusters did not correspond with family and their distances, but the grouping was in line with the genetic distances of the samples.